Bioelectric impedance overestimates the body fat in overweight and underestimates in Brazilian obese women: a comparation with Segal equation 1 - Pimentel, G. D. [UNESP] (2010)
Introduction: Overweight and obesity are risk factors to appearance of cardiovascular diseases and anthropometry is important as clinical tool for planning and health policymaking at population level. Thus, aim of this work was to compare the simple body fat percentage (%BF) obtained straight by bioeletric impedance (BIA) to the one obtained by the equation of Segal et al (1988), which uses the BIA resistance value, overweight among adult women.Methods: This study conducted with 86 adult women (50.5 +/- 11.0 years old). Body weight and height were measured and estimated the body mass index (BIND. %BF was assessed by BIA (Biodynamics (R) model 450) and Segal equation.Results: %BF derived from BIA (38.0 +/- 4.6%) and Segal et al (1988) (38.7 +/- 8.1%) were similar (p = 0.85). However, when the women were distributed, in two groups based on their BMI, overweight (n = 40; BMI = 27.3 +/- 1.2 kg/m(2)) and obesity (n = 46; BMI = 36.2 +/- 5.1 kg/m(2)), the two methods presented results significant different (p = 0.000). The %BF of overweight women was 34.6 +/- 3.6% by BIA and 30.3 +/- 2.1% when estimated by Segal equation. In obese women, the %BF was 41.0 +/- 3.0% and 46.0 +/- 2.6%, respectively.Conclusion: BIA overestimated %BF in overweight (+14.2%; +3.0 kg) and underestimated in obese (-10.9%; -4.4 kg) women.